2017
DOI: 10.1093/humrep/dex252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of randomized serum progesterone concentration on secretory endometrial histologic development and gene expression

Abstract: Supported by The Eunice Kennedy Shriver National Institute for Child Health and Disease, National Institute of Health, USA (NICHD/NIH) (R01HD067721 and U54HD30476; SLY and BAL) and Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) 240239/2012-1 (RFS). All authors have no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Morphological delay was observed in the group supplemented with lower P concentrations. Higher P levels resulted in normal histology but aberrant gene expression [20]. This experimental trial supports the clinical study of Yovich et al, which reported that the likelihood of pregnancy in cryopreserved embryo transfer cycles under hormonal control is highly dependent on the circulating concentration of P, with an optimal P concentration of 70–99 nmol/l after vaginal administration [9].…”
Section: Discussionsupporting
confidence: 77%
“…Morphological delay was observed in the group supplemented with lower P concentrations. Higher P levels resulted in normal histology but aberrant gene expression [20]. This experimental trial supports the clinical study of Yovich et al, which reported that the likelihood of pregnancy in cryopreserved embryo transfer cycles under hormonal control is highly dependent on the circulating concentration of P, with an optimal P concentration of 70–99 nmol/l after vaginal administration [9].…”
Section: Discussionsupporting
confidence: 77%
“…Thus, it seems that P resistance is not the same as P deficiency. Normal endometrium seems so robust in its ability to respond to P that endometrial histology was unchanged across a wide range of concentrations, with delayed histologic changes only seen with P concentrations below those seen in ovulatory women-although only a small number of genes showed a significant dose-response (59) (Fig. 1).…”
Section: Progesterone Action and Implantationmentioning
confidence: 99%
“…It was shown to be reduced when histology was delayed, but more importantly, when histology was ''in phase'' with b3 integrin expression expected, this integrin was lacking in clinical conditions associated with infertility, including endometriosis (76) and hydrosalpinges (77), and aberrantly expressed in a significant subset of women with unexplained infertility (78) and unexplained recurrent pregnancy loss (79). The return of normal fertility and integrin expression was demonstrated using salpingectomy (80) or treatment with an aromatase inhibitor (59). Interestingly, anb3 integrin expression is tied to the downregulation of E receptor-a, which is seen in both LPD and endometriosis.…”
Section: Endometrial Assessmentmentioning
confidence: 99%
“…24 Normal histological maturation has been demonstrated in response to very low blood levels of progesterone. 25 However, targeted gene expression analysis showed a dose-response pattern for some genes with increasing progesterone concentrations, 25 suggesting that a pre-receptive result with the ERA test corresponds to a low plasma progesterone level.…”
Section: Introductionmentioning
confidence: 99%